Why mothers do not tell : narratives of maternal non-disclosure of biological paternal identity. - Manyatshe, Livhuhani (My University, 2013)
Children with absent and unknown fathers (also referred to as undisclosed paternal identity) have distinctly been identified as an interest group due to their increased risk to adverse psychological effects specifically associated with not knowing one’s biological father. It is taken for granted that these children have the freedom of asking their mothers and female caregivers who their fathers are, not taking into account that often there is a tacit rule within these homes whereby the biological father is never discussed. The aim of this exploratory study was to use narratives of mothers and guardians who have children under their care who do not know their true fathers’ identities, in order to explore the range of probable reasons that contribute to maternal caregivers not disclosing the identity of biological fathers. Eight face-to-face, individual interviews were conducted with female participants from varying cultural and socioeconomic backgrounds within the Johannesburg area. The women aged between 33 and 60 years were recruited with the assistance of a non-governmental organisation and from online forums. Interviews were conducted in English or a language that the participants understood and lasted on average an hour. Thematic analysis was used to analyse the transcribed text. The study was undertaken using an interpretive approach that explored the phenomenon of the participants' lived experience of not disclosing. A gendered analysis provided a distanciated framework to review the findings against current societal arrangements. Findings indicated that mothers not disclosing could be linked to the fathers’ behaviour such as inconsistent commitment to the paternal role, denial of paternity and at times, whereabouts were not known limiting what could be conveyed to the children. For this particular study, the nature of the relationship, which is often characterised by the instability of the parents’ relationship at the time of the birth, and subsequent separation, seemed to be a risk factor that a child may not be told who their true father is. Gender-based violence was also found to be contributing to the separation between parents and this in turn created an opportunity for the uninvolved fathers to be absent and unknown to the children. The cultural script that silences women’s experiences of gender-based violence means that father absence that resulted from the violence was difficult to talk about in the homes. The data also gave insight into the differential experiences among the women when dealing with absent, unknown whereabouts and absconded fathers. Although this study was conducted on an exploratory basis, it is suggested that continuous engagement with this topic through research and public discourse would best define how to address the issue. The findings suggest a need to provide mothers who may be considering disclosure with strategies on how to disclose. There is also a broader need to address structural issues that may be contributing towards the phenomenon such as men's violence towards their families.
Keywords: Unknown father; Biological father; Maternal non-disclosure; Interpretive approach; Gendered analysis